Struktura szkolnictwa w imperium rosyjskim na początku XIX wieku. Zarys problemu: The structure of education in the Russian Empire at the beginning of the 19th century – outline of the issue - Szmyt, Andrzej (Przegląd Wschodnioeuropejski, 2021)
Having ascended the throne, Tsar Alexander established for the first time the Ministry of Education in 1802. Then the legal framework for the modern education in the Russian Empire was devised by a document called The Provisional Regulations of Public Enlightenment of the Russian Empire enacted 24th of January 1803, whereby six educational (school) districts were erected. The universities rode herd on schools. Next rescripts determined a.o. relations between schools and their policy. The system lasted until the fourth decade of the 19th century when Tsar started to restrict the autonomy of universities as well as unify their structure and educational system.